GALENA RADIO IN GEOGRAPHY AS A DIDACTIC-PEDAGOGICAL RESOURCE IN TEACHING-LEARNING – LISTEN BEFORE IT DISAPPEARS - de Oliveira , Érico Anderson; de Oliveira, Rosália Caldas Sanábio (Seven Editora, 2024)
This report is from an experiment with Radio Galena in the classroom with students from the initial grades of technical courses at the Federal Center for Technological Education of Minas Gerais (CEFET-MG) in Belo Horizonte. The theoretical foundation was based on a constructivist practice that proposes the articulation of knowledge from the curriculum and the ability of students to elaborate their own concepts, exercising their skills and competences. The contents of Physics (waves, resonant circuit, electromagnetism and others) and Geography (location of transmission, distance of propagation, interference of geographical features, analysis of maps, mineral resources present in the components...) were involved. During the tests, the students were able to listen to the programming of an AM radio station and correlate their listening with the contents of Geography (scale, globalization, communications, areas of influence, scope, culture, wave propagation and interference – relief, vegetation, atmospheric conditions). The prototypes were subjected to different locations to analyze the interference of geographical elements. To the geographical contents, geopolitical, physical, economic discussions etc. were added. It was found that the various contents discussed were understood in the ways in which they are articulated both for the functioning of radio, the geographical limitations, as well as for the propagation of ideas or possibilities given by technological advancement in the present day and its intercurrences of all kinds. DOI: https://doi.org/10.56238/sevened2024.037-095